Antimicrobial activity of a new class of synthetic retinoid antibiotics and comparator agents against ocular staphylococci - André, Camille; Schrank, Cassandra L.; Cheng Jaramillo, Ana Victoria; Mylonakis, Eleftherios; Wuest, William M.; Gilmore, Michael S.; Kim, Wooseong; Bispo, Paulo J. M. (Frontiers in Antibiotics, 2023)
Objectives Antimicrobial resistance is global pandemic that poses a major threat to vision health as ocular pathogens, especially staphylococcal species, are becoming increasingly resistant to first-line therapies. Here we evaluated the antimicrobial activity of a new class of synthetic retinoids in comparison to currently used antibiotics against clinically relevant ocular staphylococcal isolates. Methods Antimicrobial susceptibility testing was performed by broth microdilution for 3 novel synthetic retinoids (CD1530, CD437, and a CD437 analogue) and 7 comparator antibiotics, against a collection of 216 clinical isolates. Results CD437 MIC50 and MIC90 were 2 µg/mL for Staphylococcus aureus, and 1 µg/mL and 2 µg/mL respectively, for coagulase-negative staphylococci (CoNS). CD1530 (MIC50 = 2 µg/mL for all species) also displayed good activity with an in vitro potency slightly lower (2-fold) for S. aureus (MIC90 = 4 µg/mL) when compared to CD437. A CD437 analogue also demonstrated good in vitro activity (MIC50 = 2 µg/mL for all species) and potency (MIC90 = 2 µg/mL for MRSA and 4 µg/mL for MSSA and CoNS). In vitro potencies were similar or higher than that of comparator agents, and were not impacted by multidrug resistance phenotypes. Conclusion Our results demonstrate that synthetic retinoids display potent in vitro activity against ocular staphylococcal species, including multidrug-resistant isolates.